Borderline ankle–brachial index is associated with increased prevalence of micro- and macrovascular complications in type 2 diabetes: A cross-sectional analysis of 12, 772 patients from the Joint Asia Diabetes Evaluation Program. (September 2015) - Yan, Bryan P; Zhang, Yuying; Kong, Alice PS; Luk, Andrea OY; Ozaki, Risa; Yeung, Roseanne; Tong, Peter CY; Chan, Wing Ban; Tsang, Chiu-Chi; Lau, Kam-Piu; Cheung, Yu; Wolthers, Troels; et al.
Borderline ankle–brachial index is increasingly recognised as a marker of cardiovascular risk. We evaluated the impact of borderline ankle–brachial index in 12, 772 Chinese type 2 diabetes patients from the Joint Asia Diabetes Evaluation Program between 2007 and 2012. Cardiovascular risk factors, complications and health-related quality of life were compared between patients with normal ankle–brachial index (1.0–1.4), borderline ankle–brachial index (0.90–0.99) and peripheral arterial disease (ankle–brachial index < 0.9). The prevalence of peripheral arterial disease and borderline ankle–brachial index was 4.6% and 9.6%, respectively. Borderline ankle–brachial index patients were older, more likely to be smokers and hypertensive, had longer duration of diabetes, poorer kidney function and poorer health-related quality of life than patients with normal ankle–brachial index. After adjustment for traditional cardiovascular risk factors, borderline ankle–brachial index was an independent predictor of diabetes-related micro- and macrovascular complications including retinopathy (odd ratios: 1.19 (95% confidence interval: 1.04–1.37)), macroalbuminuria (1.31 (1.10–1.56)), chronic kidney disease (1.22 (1.00–1.50)) and stroke (1.31 (1.05–1.64)). These findings suggest that patients with diabetes and borderline ankle–brachial index are at increased cardiovascular risk and may benefit from more intensive management.